Diversity and distribution of bacteria and archaea in Tuosu Lake in Qaidam Basin - Song, Weijun; Sun, Chunyan (Cellular and Molecular Biology, 2020)
Microbes in plateau lakes are important participants of material circulation and energy flow in plateau ecosystems. Knowledge of the microbiota, such as bacteria and archaea, community distribution and diversity in plateau lakes is the basis to understand the species succession, adaptation, maintenance and metabolic mechanisms of specific environmental microbial ecosystems. This work aimed to reveal the diversity and# succession of the microbiota in Tuosu Lake to provide a biological basis for the exploration and development of microbial resources in the plateau lakes. The distribution and diversity of microflora in Tuosu Lake, hypoxia, high altitude, alkaline, closed plateau lake with fresh water supply, was investigated. The total DNA was extracted from six samples with different salinity from different geographical locations of Tuosu Lake. The 16S rRNA gene of bacteria and archaea were determined by using high-throughput sequencing-based on an Illumina Miseq sequencing platform. The microbiota in Tuosu Lake has a high diversity and complexity and there are a large number of unclassified microbial species. The bacterial communities in Tuosu Lake are dominated by Proteobacteria (44.3%) and Actbacteria (17.2%). Among them, Î²-Proteobacteria is the dominant genus in the low-salt sample, while Î³-Proteobacteria is more advantageous in the samples with higher salinity. The archaeal communities are dominated by Euryarchaeota (50%) and Woesearchaeota__DHVEG-6 (42.6%). The vast majority of the methanogenic archaea in Tuosu Lake samples belong to Methanomicrobia, and the methanogens in low-salinity samples are significantly more abundant than those in high-salt samples. Diversity and distribution appear to be highly influenced by water salinity and pH.